Investor behaviour and investment decisions: Evidence from Pakistan Stock Exchange - Muhammad Ali,; Nayeem ul Hassan Ansari,; Bilal Ahmed Chishty,; Chin-Hong Puah,; Muhammad Ashfaq, (Asian Academy of Management Journal, 2023)
This research aims to understand the influence of behavioural factors on investment decisions in the Pakistan Stock Exchange (PSX). This study gathered primary data using a survey-based questionnaire from 318 individual investors. The issue being investigated in this study is how behavioural elements, such as sentiment, overconfidence, over- and under-reaction, and perceived market efficiency, affect investment choices made on the PSX, with a particular emphasis on the limited predictive power of herd behaviour. The sample data were analysed using partial least square-structural equation modelling (PLS-SEM) based approach. Results indicate that financial knowledge, sentiment, overconfidence, over- and under-reaction, and perceived market efficiency significantly affect the investment decision. Interestingly, herd behaviour does not play a significant role in predicting investment decisions. However, we are certain that this study will provide a better understanding of the relationship between behavioural factors and an investor’s investment decision in Pakistan.